(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Dustbins (or Garbage Bins, Trash Cans, whatever you name them) are small containers of plastic or metal used on a temporary basis to store trash (or waste). They are also used for the collection of waste in houses, workplaces, highways, parks, etc. Littering is a major crime in some countries, and public waste bins are also the only way to dispose of small waste. Usually, using different bins for handling wet or dry, recyclable or non-recyclable waste is a common practice. From an ETS perspective, smart waste collection can help municipalities and private waste management companies avoid the need for collection sites, waste disposal facilities and waste treatment plants. As communities increasingly rely on smart city technology to improve, among other things, the quality of life of their residents and the environment, city leaders recognize that smart waste management can also help them achieve sustainability goals such as zero waste and improve services to residents, while improving service to residents. As an example, Development of Some solar-powered bins and recycling bins are already equipped with sensors that analyze data on what is disposed of or recycled and notify collectors when the bin is too full and needs to be picked up. These developed Smart waste management solutions use sensors placed in waste bins to measure levels, notify municipal waste collection services, when the bins are ready to be emptied, and also notify municipal waste collection with a ton has been emptied. Therefore, the solar-powered of sensors based smart waste monitoring system is more and more useful to the current smart cities policies under the smart city project works.